Trafficking: Design for the Viral Exchange of TV Content on Mobile Phones - Harper, Richard; Regan, Tim; Izadi, Shahram; Mosawi, K.; Rubens, S.; Rouncefield, M. (Association for Computing Machinery, Inc., 2008)
In this paper, we report, first of all, the discovery of a particular kind of emerging social practice involving the exchange of multimedia content on mobiles that we label ‘trafficking’. Second, the iteration of a design solution to extend these practices to include the trafficking of broadcast TV content ‘segments’. Third, the implications this had for basic assumptions in the interaction design afforded by the two primary OS’s in the mobile handset domain. And, fourth, the legal and business inhibitors-enablers that affected not only this research but which are likely to affect all attempts to stretch the capacity of mobile devices and mobile interaction design to afford new ways of ‘trafficking’ multimedia content.